Webinar Huawei Student Developer UMP - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 4 August 2021 - A webinar was organised by FK in collaboration with Huawei on 'The Future of Mobile App Industry' on 4th August 2021, virtually.